Financial Aid, Borrowing Constraints, and College Attendance: Evidence from Structural Estimates - Keane, Michael P (American Economic Review, 2002)
Financial Aid, Borrowing Constraints, and College Attendance: Evidence from Structural Estimates by Michael P. Keane. Published in volume 92, issue 2, pages 293-297 of American Economic Review, May 2002